Fabrication and electrical properties of Pb(Co1/3Nb2/3)O3 ceramics - M. Unruan (2018)
Pb(Co1/3Nb2/3)O3 (PCN) ceramics have been produced by sintering PCN powders synthesized from lead oxide (PbO) and cobalt niobate (CoNb2O6) with an effective method developed for minimizing the level of PbO loss during sintering. Attention has been focused on relationships between sintering conditions, phase formation, density, microstructural development, dielectric and ferroelectric properties of the sintered ceramics. From X-ray diffraction analysis, the optimum sintering temperature for the high purity PCN phase was found at approximately 1050 and 1100 °C. The densities of sintered PCN ceramics increased with increasing sintering temperature. However, it is also observed that at very high temperature the density began to decrease. PCN ceramic sintered at 1050 °C has small grain size with variation in grain shape. There is insignificant change of dielectric properties with sintering temperature. The P-E hysteresis loops observed at -70 °C are of slim-loop type with small remanent polarization values, which confirmed relaxor ferroelectric behavior of PCN ceramics. © 2008 Elsevier Ltd and Techna Group S.r.l.